The Results on the Existence of Fixed Points in Hilbert Spaces via Functions of Class $C$ - Mana Donganont; Arsalan Ansari; Snjezana Maksimovic; Zoran Mitrovic (Sahand Communications in Mathematical Analysis)
In this paper, we obtain a result on the existence of fixed points in Hilbert space using functions of class $C$. Recently, Chouhan and Desai published a paper [Some Common Fixed-Point Theorems in Hilbert Space, J. Eemerg. Technol. Innov. Res., 2022, 9(10), 1-12]. We observed an error in the proof of Theorem 3.2 on page d316 of their paper. Using the $C$-class of functions, we have corrected this error and improved  their result.